Insight into the da Vinci® Xi – technical notes for single‐docking left‐sided colorectal procedures. Issue 4 (23rd December 2016) - Ngu, James Chi‐Yong; Sim, Sarah; Yusof, Sulaiman; Ng, Chee‐Yung; Wong, Andrew Siang‐Yih
Abstract: Background: The adoption of robot‐assisted laparoscopic colorectal surgery has been hampered by issues with docking, operative duration, technical difficulties in multi‐quadrant access, and cost. The da Vinci® Xi has been designed to overcome some of these limitations. We describe our experience with the system and offer technical insights to its application in left‐sided colorectal procedures. Methods: Our initial series of left‐sided robotic colorectal procedures was evaluated. Patient demographics and operative outcomes were recorded prospectively using a predefined database. Results: Between March 2015 and April 2016, 54 cases of robot‐assisted laparoscopic left‐sided colorectal procedures were successfully completed with no cases of conversion. The majority were low anterior resections for colorectal malignancies. Using the da Vinci® Xi Surgical System, multi‐quadrant surgery involving dissection from the splenic flexure to the pelvis was possible without redocking. Conclusions: The da Vinci® Xi simplifies the docking procedure and makes single‐docking feasible for multi‐quadrant left‐sided colorectal procedures.